2017
DOI: 10.2298/gensr1703001h
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and combining ability of some important traits in rice (Oryza sativa L.)

Abstract: In order to study the combining ability, genetic parameters and gene actions of yield, yield components and quality characters in rice, fifteen F2 generation of a 6×6 diallel cross, excluding reciprocals, was grown in a randomized complete block design (RCBD) with three replications. The results of analysis of variance showed significant differences between the genotypes for grain yield (GY), 100-grain weight (HGW), number of panicles per plant (PN), panicle length (PL), number of full grains per panicle (FGN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The similar low and high heritability of panicle and yield related traits were observed by Gunasekaran et al (2020), Haghighi et al (2017) and Bassuony and Zsembeli (2021). The Vr-Wr graph showed that, for the number of spikelets per panicle, the number of filled grains per panicle and the number of secondary branches per panicle, the regression line passed above the origin, proving that these traits were governed by partial dominance and for grain yield per plant the regression line passed below the origin showed the existence of over dominance effect (Fig.…”
Section: Resultssupporting
confidence: 68%
“…The similar low and high heritability of panicle and yield related traits were observed by Gunasekaran et al (2020), Haghighi et al (2017) and Bassuony and Zsembeli (2021). The Vr-Wr graph showed that, for the number of spikelets per panicle, the number of filled grains per panicle and the number of secondary branches per panicle, the regression line passed above the origin, proving that these traits were governed by partial dominance and for grain yield per plant the regression line passed below the origin showed the existence of over dominance effect (Fig.…”
Section: Resultssupporting
confidence: 68%
“…2021, 25(3): 7-25 Issn 0188789-0 genes con efectos dominantes; además, está positivamente correlacionado con caracteres como el largo, ancho, la relación largo/ancho y grosor de grano (Huang et al, 2013). Haghighi et al (2017), encontraron diferencias significativas según el cálculo de HCG y HCE para las variables productividad, granos por panícula, peso de 1 000 granos, panículas por planta, contenido de amilosa y consistencia gelatinosa del grano, resultados que concuerdan con lo obtenido en la presente investigación, donde las variables granos por panícula, peso de 1 000 granos y panículas por planta fueron significativas y presentaron variación entre parentales y cruces.…”
Section: Determinación De La Heterosis Media Obtenida En Los Híbridos...unclassified
“…Rice is the second important crop in the world consumed by half of the world's population (Haghighi et al, 2017). FAO estimates revealed that world rice production in 2011 was 720 million tonnes and global production in 2025 should reach 800 million tonnes to meet global consumption (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%